A Clinicopathologic Study and Descriptive Analysis of "Atypical Endosalpingiosis". (May 2020) - Talia, Karen L.; Fiorentino, Lisa; Scurry, James; McCluggage, W. Glenn
Abstract : "Atypical endosalpingiosis" (AE) is a diagnostic term used variably among pathologists to denote peritoneal lesions exhibiting architectural changes and/or cytologic atypia intermediate between endosalpingiosis and primary peritoneal serous borderline tumor (SBT). AE is a contentious entity and is not recognized in the current World Health Organisation Classification. We report a series of 10 cases classified as AE, in attempt to further characterize this lesion. The patients ranged in age from 24 to 72 yr (mean, 39.7 yr) and the commonest presenting complaint was abdominal pain. Operative findings usually comprised small peritoneal nodules and/or fibrous adhesions, predominantly involving the pelvis. The lesions were either mesothelial or submesothelial in location and typically exhibited mixed tubular and papillary architecture, sometimes with minor components of solid, cribriform or single cell growth. Epithelial multilayering was present in all cases but usually involved <25% of the lesion. There was mild nuclear atypia and mitoses were infrequent or absent. No infiltrative growth was seen. The stroma was usually inflamed and psammoma bodies were consistently present. Features which prompt a diagnosis of AE rather than endosalpingiosis include architectural alterations, usually in the form of papillae, epithelial multilayering, and mild nuclear atypia. While the extent of these findings is often less than occurs in primary peritoneal SBT or in extraovarian implants in association with an ovarian SBT, robust histologic criteria for distinction of AE from SBT do not exist. Despite this, the term AE may be of use when dealing with atypical peritoneal proliferations resembling SBT but which are limited in extent or fall just short of criteria for an unequivocal diagnosis of primary peritoneal SBT. In our series, lesions diagnosed as AE did not result in adverse clinical outcome (follow-up in 8 patients from 4 to 84 mo). Further study is required to determine whether a diagnostically reproducible and clinically relevant intermediate lesion exists between endosalpingiosis and SBT.